Risk Assessment And HACCP-Based Hazard Control in Malt Candyprocessing - Ermawati Ermawati (Agroindustrial Technology Journal, 2025)
Malt candy is a type of hard confectionery product formulated with the addition of specific leavening agents that, during the heating (oven) process, produce a light, porous, and melt-in-the-mouth texture. The safety and quality of malt candy are strongly affected bythe hygienic conditions of the production environment, process parameters, and raw material handling. Therefore, the of the HACCP system plays an essential rolein identifying and controlling potential hazards at every stage of the manufacturing process.This study aims to perform a comprehensive risk assessment and apply HACCP-based hazard control measures in the malt candy production line. The research involves developing a detailed process flow diagram, identifying potential biological, chemical, and physical hazards,determining(CCPs)establishing critical limits, and formulating monitoring and corrective action procedures. Data were collected through on-site observation, environmental inspection, and evaluation of production records to assess risk levels and compliance with HACCP principles.The findings indicate that the primary Critical Control Point (CCP) is located at the inspection stage, where a metal detector is employed to ensure that the product is free from metallic contaminants and compliant with food safety requirements. Furthermore, the results suggest that metal contamination control should not only be addressed at the CCP level, but also reinforced as a Control Point within the prerequisite program (CPP), thereby enabling corrective actions to be properly traced and theireffectiveness continuously evaluated. Accordingly, it is recommended that the company strengthen documentation, verification activities, and equipment maintenance at this stage as part of ongoing improvements in the implementation of the prerequisite (basic feasibility) program. This approach ensures that the application of HACCP is not merely reactive, but also preventive, measurable, and fully accountable through a clear audit trail, serving as a reference model for similar confectionery industries. Keywords : CCP, HACCP, Malt Candy, Metal Contamination, Risk Assessment